FIELD ENVIRONMENTAL PHILOSOPHY AND THE SUB-ANTARCTIC ECOREGION OF MAGALLANES AS A NATURAL LABORATORY IN THE ANTHROPOCENE - Rozzi Marin, Ricardo Roberto (My University, 2018)
This special issue of Magallania presents the methodological approach of the Field Environmental Philosophy (FEP). I propose that to implement the concept of natural laboratory recently proposed by the State of Chile, it is fundamental to strengthen the activity of laboring with a transdisciplinary approach in these places. FEP offers a methodology and an understanding that open scientific, cultural and ethical horizons to consolidate as a natural laboratory the sub-Antarctic Magellanic ecoregion and the Cape Horn Biosphere Reserve, whose attributes are presented in the first part of this special issue. In addition, FEP's methodology can be adapted to work in other natural laboratories in Chile and the world. Today this is especially relevant in the context of the Anthropocene that has dissolved the old dichotomies between "biophysical" and "cultural" dimensions of reality and demands a sense of ethical responsibility. To respond to the socio-environmental challenges of the Anthropocene, FEP proposes a methodological approach that integrates the theoretical framework of the biocultural ethic and diverse forms ecological knowledge of indigenous peoples and modern sciences, arts and philosophy into biocultural research, education, and conservation practices. FEP represents a socio-ecological innovation since this methodology has allowed to systematically interrelate concepts and practices of the sciences and ethics into school and higher education programs, and is being adapted into biosphere reserves and long-term socio-ecological study sites. These sites provide a valuable institutional platform to transform development policies and homogeneous educational programs that today are imposed globally on various habitats and life habits, and reorient them towards a higher valuation of the vital relationships that exist between lifestyle habits and specific habitats that are shared by communities of co-inhabitants. As discussed in the second and third parts of this volume, FEP provides a practical understanding to consider ourselves as co-inhabitants (not mere human resources or natural resources), a concept that provides an understanding of the dignity of diverse living beings and diverse cultures.
Keywords: biocultural conservation; biocultural ethics; biosphere reserve; education; long-term socio-ecological research (ltser)